2023
DOI: 10.1002/nop2.1729
|View full text |Cite
|
Sign up to set email alerts
|

Health care Professionals' experiences of counselling competence in digital care pathways – A descriptive qualitative study

Abstract: Aim: Health care professionals are tasked with the role of supporting patients in using eHealth services in their personal care and counselling competence in digital environments to ensure appropriate patient care. Our aim was to describe health care professionals' experiences of counselling competence in Digital Care Pathways.Design: A descriptive qualitative study. Methods:Interviews with semi-structured questions were conducted. Twelve healthcare professionals were interviewed. The data were analysed using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
0
0
Order By: Relevance
“…In our study, Ensuring a competent and knowledgeable experience and competencies of HCPs were identified as significant contributors to healthcare quality. Similar outcomes were also identified in a study by Kaihlaniemi et al (2023) that examined the relationship between nurse staffing and patient outcomes. The study found that hospitals with a higher proportion of nurses with a Bachelor of Science in Nursing (BSN) degree had lower mortality rates and better patient outcomes.…”
Section: Discussionsupporting
confidence: 71%
“…In our study, Ensuring a competent and knowledgeable experience and competencies of HCPs were identified as significant contributors to healthcare quality. Similar outcomes were also identified in a study by Kaihlaniemi et al (2023) that examined the relationship between nurse staffing and patient outcomes. The study found that hospitals with a higher proportion of nurses with a Bachelor of Science in Nursing (BSN) degree had lower mortality rates and better patient outcomes.…”
Section: Discussionsupporting
confidence: 71%
“…This finding is also supported by previous research as healthcare professionals, specifically nurses, evaluated their competence in working in a digital environment as low (Kujala et al, 2018;Saranto et al, 2022). Counselling in digital environments has become an important channel in patient care delivery (Kaihlaniemi et al, 2023). In our study, this includes the competence to guide and support patients to use digital services according to their needs, communicate with patients using digital solutions, and work in the digital healthcare environment.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, this includes the competence to guide and support patients to use digital services according to their needs, communicate with patients using digital solutions, and work in the digital healthcare environment. Lower competence in remote counselling could be argued to be explained by lack of training (Kujala et al, 2018) and therefore expertise in the area (Kaihlaniemi et al, 2023), but also the fact that not necessarily all respondents use remote counselling or digital environments in…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations